2022
DOI: 10.1186/s12888-022-03963-7
|View full text |Cite
|
Sign up to set email alerts
|

High neutrophil-to-lymphocyte ratio is a significant predictor of depressive symptoms in maintenance hemodialysis patients: a cross-sectional study

Abstract: Background Depression is one of the most important psychiatric disorders in chronic kidney disease patients who undergo maintenance hemodialysis (MHD). Previous studies have shown that low-grade inflammation is involved in the progression of depressive symptoms. The neutrophil-to-lymphocyte ratio (NLR) is an inflammatory marker that is inexpensive and easy to measure. However, the association between NLR and depression symptoms in MHD patients has not been examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Previous study has investigated the correlation between depression status and in ammation index in MHD patients, indicating that high NLR is an independent risk factor for depression scores in MHD patients and can be used to predict depression status in MHD patients [40]. This study reports for the rst time the correlation between SII and depressive status in MHD patients, and the results show that high SII is an independent risk factor for depressive status in MHD patients.…”
Section: Discussionmentioning
confidence: 61%
“…Previous study has investigated the correlation between depression status and in ammation index in MHD patients, indicating that high NLR is an independent risk factor for depression scores in MHD patients and can be used to predict depression status in MHD patients [40]. This study reports for the rst time the correlation between SII and depressive status in MHD patients, and the results show that high SII is an independent risk factor for depressive status in MHD patients.…”
Section: Discussionmentioning
confidence: 61%
“…[12] Research by Feng shows that the red cell distribution width (RDW) is related to depressive symptoms, where the group with mild depressive symptoms is found to be higher than the group without depressive symptoms. [13] However, another study that compared individuals with depressive symptoms with those without any mental illness reported that there was no significant difference in the RDW values of the two groups. This could be due to differences in the number of study samples, thereby reducing statistics significance.…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al [ 46 ] found an association between NLR and clinically relevant depressive symptoms in people with diabetes. In a cross-sectional study, Feng et al [ 47 ] found high NLR is a significant predictor of depressive symptoms in patients. There are also works contradicting the relationship between NLR and depression.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies that have shown an association between inflammation and depression in the general population. [ 46 , 47 ] ROC analysis determined that an NLR cutoff of 3.26 had 88.2% specificity and 48.6% sensitivity in distinguishing between depression groups. Patients with an NLR higher than 3.26 were approximately 6.1 times more likely to belong to the moderate or major depression group than those with a lower NLR.…”
Section: Discussionmentioning
confidence: 99%